Process for recovering antimony white from low-purity antimony oxide powder by removing arsenic

CN122877802APending Publication Date: 2026-10-09HUNAN HUAXIN RAREANDPRECIOUS METALS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611337846.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-31
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

其一,收尘方式落后,选择性分离能力不足:传统工艺多采用电收尘器对锑氧粉烟气进行收尘,电收尘依赖粉尘在高压电场中的荷电差异实现分离,但锑氧粉(Sb2O3)与砷氧粉(As2O3)的荷电特性差异有限,导致收尘选择性差,大量有价金属锑随烟气流失,最终产品中Sb2O3品位低,锑回收率低,产品品位难以满足高端阻燃剂市场对锑白纯度≥99.0%的要求

Benefits of technology

1.砷脱除率和锑回收率显著提高:本发明采用极性选择性覆膜布袋替代传统电收尘,利用收尘温度下Sb2O3固态微粒与As2O3气态的相态差异,结合覆膜表面的极性低粘附特性实现选择性分离,从根本上改变了传统收尘设备仅依赖粒径或荷电差异的分离机理。经实施例验证,本发明锑白产品中Sb2O3质量分数由原料粉尘中的62.5%提升至76.8-80.1%,Sb2O3回收率达到79.5%-81.0%,As2O3脱除率达到90.2%-92.8%。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application provides a process for removing arsenic and recovering antimony white from low-purity antimony oxygen powder, and relates to the technical field of non-ferrous metallurgy. The process steps include: low-purity antimony oxygen powder flue gas is sent into a special film-coated bag dust collection system for primary dust collection after being cooled to 280-310 DEG C by air, and then the flue gas after dust collection is sent into a multi-stage gradient air quenching tower, and is rapidly quenched to 255-265 DEG C and then slowly cooled to 150-160 DEG C; the flue gas after cooling is sent into a secondary bag dust collection system to recover antimony oxygen dust. The special film-coated bag has a surface polarity control type composite coating material, and an organic polymer modified component containing an aromatic large side group and a polar functional group is dispersed in a polytetrafluoroethylene matrix to form a polar enrichment micro area on the film surface, so that the Sb2O3 particles are efficiently captured and the As2O3 gas has low adhesion and low retention. The gradient air cooling inhibits the generation of As2O3 glass and induces the precipitation of crystal. The mass fraction of Sb2O3 in the antimony white product is increased from 62.5% in the raw material dust to 76.8-80.1%, the Sb2O3 recovery rate reaches 79.5%-81.0%, and the As2O3 removal rate reaches 90.2%-92.8%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of non-ferrous metal metallurgy, and in particular to a process for removing arsenic and recovering antimony white from low-purity antimony oxygen powder. Background Technology

[0002] Antimony white (Sb₂O₃) is an important deep-processed antimony product, widely used in flame retardants, catalysts, ceramic pigments, and other fields. During antimony smelting, the flue gas generated from the volatilization roasting or smelting of antimony-containing materials is treated with dust to obtain antimony oxide powder. However, because antimony ore often contains impurities such as arsenic, lead, and bismuth, arsenic and antimony oxides volatilize simultaneously into the flue gas during volatilization, resulting in low-grade antimony oxide powder with high arsenic content obtained from dust collection. This severely affects the quality and application of subsequent antimony white.

[0003] The existing process for removing arsenic and recovering antimony white from low-purity antimony oxide powder has the following problems: Firstly, the dust collection methods are outdated and lack selective separation capabilities: Traditional processes often use electrostatic precipitators (ESPs) to collect dust from antimony-oxygen powder flue gas. ESPs rely on the difference in charge of dust particles in a high-voltage electric field for separation. However, the difference in charge characteristics between antimony-oxygen powder (Sb₂O₃) and arsenic-oxygen powder (As₂O₃) is limited, resulting in poor dust collection selectivity. A large amount of valuable antimony is lost with the flue gas, leading to low Sb₂O₃ content and low antimony recovery rate in the final product. This makes it difficult to meet the requirements of the high-end flame retardant market for antimony white purity ≥99.0%. Simultaneously, ESPs have low efficiency in capturing fine dust, resulting in resource waste and environmental pollution.

[0004] Secondly, the flue gas cooling method is unreasonable, and the system is severely corroded: In order to quickly reduce the temperature of flue gas, traditional processes often use direct spray cooling with process water. However, water spray cooling has serious drawbacks. For example, if the flue gas contains acidic components such as SO2, SO3, As2O3, and HCl, the sprayed water will form corrosive condensates such as sulfuric acid, sulfurous acid, and arsenic acid, which will significantly increase the corrosivity of the flue gas, accelerate the corrosion and failure of pipelines, dust collection equipment, and induced draft fans, resulting in frequent equipment maintenance, high maintenance costs, and a significant reduction in the overall service life of the system.

[0005] Thirdly, the problem of arsenic oxide glassy blockage is prominent: When As2O3 condenses and crystallizes in the temperature range of 170-270℃, it forms an amorphous, colorless, and colorless glassy substance (commonly known as "arsenic glass"). This glassy substance has extremely strong adhesive properties, easily adhering to the inner walls of pipes, elbows, valves, and dust collection equipment inlets. It is also hard and chemically stable, making it difficult to remove by conventional mechanical knocking or water flushing. The gradual accumulation of this glassy substance leads to a continuous increase in system ventilation resistance and energy consumption. In severe cases, it can completely block the pipes, forcing the system to shut down for cleaning, seriously restricting production continuity and economic efficiency.

[0006] Fourth, existing filter materials struggle to balance temperature resistance and selectivity: some improved processes attempt to replace electrostatic precipitators with high-temperature filter media baghouses, but conventional high-temperature filter media rely solely on particle size sieving to capture dust, failing to achieve selective separation of arsenic and antimony oxides. Furthermore, high-temperature filter media have limited tolerance to low-melting-point impurities such as sodium, magnesium, and lead in flue gas. When the total proportion of impurities in the raw material exceeds a certain limit, "bag clogging" easily occurs on the filter media surface, leading to a sharp increase in system operating resistance.

[0007] Therefore, developing a low-purity antimony oxygen powder process for arsenic removal and antimony white recovery that combines high dust collection efficiency, high arsenic and antimony separation selectivity, good temperature resistance and corrosion resistance, and long-term operational stability is a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0008] In view of this, the present invention proposes a process for removing arsenic and recovering antimony white from low-purity antimony oxide powder, thereby solving the above-mentioned problems. The technical solution of the present invention is implemented as follows: A process for removing arsenic and recovering antimony white from low-purity antimony oxide powder includes the following steps: (1) One-time dust collection The low-purity antimony oxygen powder flue gas is cooled to 280-310℃ by air and then sent into a special membrane-coated bag dust collection system for primary dust collection to recover Sb2O3 dust. The coating layer of the special coated bag is a surface polarity-controlled composite coating material. The composite coating material includes polytetrafluoroethylene body and an organic polymer modified component dispersed in the polytetrafluoroethylene body. The molecular chain of the organic polymer modified component contains aromatic large side groups and polar functional groups. (2) Gradient air cooling The flue gas discharged after dust collection in step (1) is sent into a multi-stage gradient air quench tower, and the air is used as the cooling medium to perform gradient cooling to 150-160℃. (3) Secondary dust collection The cooled flue gas from step (2) is sent to a baghouse dust collection system for secondary dust collection to recover antimony-oxygen dust and obtain antimony white product.

[0009] The low-purity antimony-oxygen powder flue gas of this invention is taken from the exhaust duct at the top of the volatilization furnace in an antimony smelter, and the flue gas temperature is approximately 850°C. The dust concentration in the flue gas is 48-52 g / Nm³. 3 The chemical composition of the dust (by mass fraction) is as follows: Sb₂O₃ 62.5%, As₂O₃ 14.2%, Bi₂O₃ 1.8%, PbO 4.5%, Na₂O 2.3%, MgO 1.6%, SiO₂ 8.5%, with the remainder being the balance.

[0010] Bi₂O₃ and PbO, when converted to elemental Bi and Pb, account for approximately 1.61% and 4.18%, respectively.

[0011] Furthermore, in step (1), the aromatic macroside group is selected from at least one of phenyl, naphthyl, fluorenyl and triphenylmethane.

[0012] Furthermore, in step (1), the polar functional group is selected from at least one of sulfone, imide, and trifluoromethyl.

[0013] Furthermore, in step (1), the micropore diameter of the coating layer is 0.1-3.5 μm and the porosity is 75-90%.

[0014] Furthermore, in step (1), the organic polymer modified component accounts for 8-15% of the total mass of the coating layer, and the polytetrafluoroethylene vinyl body accounts for 85-92% of the total mass of the coating layer; the organic polymer modified component forms polar enrichment micro-regions in the coating layer.

[0015] The aromatic large side groups of this invention possess a large spatial volume and rigid structure. During the blending of the modified component with polytetrafluoroethylene vinyl body to form a film, the steric hindrance effect of the large side groups expands adjacent polymer molecular chains, increasing the spacing between molecular chains and the degree of stacking disorder, creating a large proportion of "free volume" microregions inside and on the surface of the material. Simultaneously, the polar functional groups of this invention (sulfone groups, imide groups, trifluoromethyl groups, etc.) have high dipole moments, forming localized strongly polar regions around the free volume microregions. The superposition of these two effects results in the formation of numerous nanoscale "polar enrichment microregions" on the coating surface.

[0016] At the initial dust collection inlet temperature, Sb₂O₃ in the flue gas exists as solid particles, while As₂O₃ exists in gaseous form. When arsenic-antimony-containing flue gas passes through the membrane, the membrane efficiently captures and recovers the solid Sb₂O₃ particles, yielding Sb₂O₃ dust. Simultaneously, the polar enrichment micro-regions formed on the membrane surface exhibit low wetting and low adhesion characteristics, resulting in low adhesion and low retention of gaseous As₂O₃ and arsenic-containing fine powder that may condense in local low-temperature areas. This prevents As₂O₃ from being adsorbed, condensed, and enriched on the membrane surface and within the pores, allowing it to smoothly pass through the membrane with the flue gas into the subsequent gradient air cooling system. This avoids the accumulation of arsenic-containing dust on the membrane surface, preventing "bag clogging" and arsenic glass adhesion, and ensuring the long-term stable operation of the membrane-coated bag filter. This achieves selective separation of arsenic and antimony; solid Sb₂O₃ is captured and recovered by the membrane, while gaseous As₂O₃ is directionally transferred to the subsequent stage, where it precipitates as crystals and is removed by gradient cooling.

[0017] Furthermore, in step (1), the inlet temperature of the primary dust collector is 295-305℃.

[0018] Furthermore, in step (2), the gradient cooling specifically involves: First stage rapid cooling: The flue gas is rapidly cooled from 280-310℃ to 255-265℃, with a cooling rate of 10-15℃ / s and a residence time of ≤1.5s; The second stage of slow cooling: the flue gas is slowly cooled from 255-265℃ to 150-160℃ at a cooling rate of 1-2℃ / s.

[0019] Furthermore, in step (2), the low-grade As2O3 dust that has settled at the bottom of the air quench tower is recovered.

[0020] Furthermore, in step (3), the antimony white product contains 74%-81% Sb2O3, 3%-5% As2O3, 0.02%-0.4% Bi, and 0.1%-1% Pb.

[0021] In the gradient air cooling step of this invention, the flue gas is first rapidly cooled from the dust collection temperature to 255-265°C in the first stage of rapid cooling, quickly crossing the high temperature zone of glassy state at the onset of As2O3 condensation (about 270°C), shortening the residence time of As2O3 in this temperature zone and inhibiting the large-scale formation of amorphous glass. Then, it is slowly cooled from 255-265°C to 150-160°C in the second stage of slow cooling at a rate of 1-2°C / s. The slow cooling within the As2O3 condensation and precipitation range is conducive to the growth of As2O3 crystal nuclei, preferential precipitation in crystalline form and sedimentation at the bottom of the tower, further reducing the arsenic content in the flue gas, and at the same time reducing the glassy adhesion on the inner wall of the downstream pipeline.

[0022] Compared with the prior art, the beneficial effects of the present invention are: 1. Significantly improved arsenic removal and antimony recovery rates: This invention uses polar-selective coated bags to replace traditional electrostatic precipitators. Utilizing the phase difference between solid Sb₂O₃ particles and gaseous As₂O₃ at the collection temperature, combined with the polar, low-adhesion characteristics of the coated surface, selective separation is achieved. This fundamentally changes the separation mechanism of traditional dust collection equipment, which relies solely on particle size or charge differences. Verification through examples shows that the Sb₂O₃ mass fraction in the antimony white product of this invention is increased from 62.5% in the raw material dust to 76.8-80.1%, the Sb₂O₃ recovery rate reaches 79.5%-81.0%, and the As₂O₃ removal rate reaches 90.2%-92.8%.

[0023] 2. Strong System Adaptability: The special membrane-coated bag filter achieves selective separation based on the phase difference between Sb₂O₃ solid particles and As₂O₃ gaseous state at the dust collection temperature, combined with the low adhesion polarity of the membrane surface. It is unaffected by the particle charge state and has a low rejection rate for non-polar or weakly polar impurities such as sodium, magnesium, and lead salts, avoiding the accumulation of impurities on the filter media surface and the problem of "bag clogging." This invention's process can adapt to complex operating conditions where the total proportion of sodium, magnesium, and lead impurities in flue gas raw materials does not exceed 17%, significantly broadening the applicable range of raw materials.

[0024] 3. Extended System Operating Cycle: Gradient air cooling technology, through a dual mechanism of rapidly traversing the glassy sensitive temperature range and inducing crystalline precipitation through slow cooling, inhibits the formation and deposition of As2O3 glass at its source. Experiments show that after adopting the gradient air cooling scheme of this invention, the continuous operating cycle of the system is extended from 15 days in the traditional single-stage quench process to over 45 days, significantly reducing the frequency of downtime for cleaning and blockage removal, and improving production efficiency and economic benefits.

[0025] 4. Reduced equipment corrosion: Using air as the cooling medium instead of water spraying in traditional processes fundamentally avoids the generation of acidic condensate, eliminating the chemical and electrochemical corrosion of pipes, housings, fans, and other equipment by corrosive liquids. This reduces the frequency of equipment maintenance and extends the overall service life of the system.

[0026] 5. Simple process flow and low investment and operating costs: Based on the traditional "dust collection-cooling-dust collection" process, this invention can be achieved simply by improving the material of the membrane bag and optimizing the process parameters of the quench tower structure. No new complex equipment is required, the modification cost is low, and it is easy to promote and apply. Detailed Implementation

[0027] To better understand the technical content of this invention, specific embodiments are provided below to further illustrate the invention.

[0028] Unless otherwise specified, the experimental methods used in the embodiments of this invention are all conventional methods.

[0029] Unless otherwise specified, all materials and reagents used in the embodiments of this invention are commercially available.

[0030] The low-purity antimony-oxygen powder flue gas of this invention is taken from the exhaust duct at the top of the volatilization furnace in an antimony smelter, and the flue gas temperature is approximately 850°C. The dust concentration in the flue gas is 52 g / Nm³. 3 The chemical composition of the dust (by mass fraction) is as follows: Sb₂O₃ 62.5%, As₂O₃ 14.2%, Bi₂O₃ 1.8%, PbO 4.5%, Na₂O 2.3%, MgO 1.6%, SiO₂ 8.5%, with the remainder being other impurities (mainly Fe, Cu, etc., totaled to 100%). Bi₂O₃ and PbO, converted to elemental Bi and Pb, are approximately 1.61% and 4.18%, respectively. In the product of this invention, Bi and Pb are calculated as elements.

[0031] Example 1 A process for removing arsenic and recovering antimony white from low-purity antimony oxide powder includes the following steps: (1) One-time dust collection The low-purity antimony oxygen powder flue gas discharged from the volatilization furnace of the antimony smelter is naturally cooled to 300°C by air and then sent to a special membrane-coated bag dust collection system for primary dust collection to recover Sb2O3 dust. The bag filter velocity is 0.8 m / min and the dust removal method is pulse jet cleaning.

[0032] The coating layer of the special coated fabric bag used is a surface polarity-controlled composite coating material, specifically composed of: a polytetrafluoroethylene (PTFE) matrix, accounting for 88% of the total mass of the coating layer; and an organic polymer modification component (with polysulfone polymers as the main chain, phenyl side groups, and containing sulfone functional groups), accounting for 12% of the total mass of the coating layer. The micropore size distribution of the coating layer is 0.5-2.5 μm, and the porosity is 85%. The organic polymer modification component is uniformly dispersed in the PTFE matrix at a size of 100-300 nm, forming nanoscale polar enrichment micro-regions on the coating surface.

[0033] (2) Gradient air cooling: The flue gas (temperature 295℃) discharged after dust collection in step (1) is sent into a two-stage gradient air quench tower for gradient cooling using ambient temperature air as the cooling medium: First stage rapid cooling: The flue gas is rapidly cooled from 295℃ to 260℃ at a cooling rate of 10℃ / s, with a residence time of 1.1s; The second stage of slow cooling: the flue gas is slowly cooled from 260°C to 155°C at a cooling rate of 1.5°C / s; Low-grade As2O3 dust that settles at the bottom of the air quench tower is recovered.

[0034] (3) Secondary dust collection: The flue gas cooled to 155°C in step (2) is sent to a pulse bag dust collection system for secondary dust collection. The filtration velocity is 0.6 m / min. Antimony-oxygen dust is recovered to obtain the final antimony white product.

[0035] Product performance testing The composition of the final antimony white product of Example 1 was analyzed by X-ray fluorescence spectroscopy (XRF) and inductively coupled plasma mass spectrometry (ICP-MS), and the results are shown in Table 1.

[0036] Table 1

[0037] Note: Other components mainly consist of Na2O, MgO, SiO2, and small amounts of Fe, Cu, and other impurities, totaling 100%.

[0038] Based on material balance calculations, the Sb₂O₃ recovery rate in Example 1 was 80.2%, and the As₂O₃ removal rate was 91.5%. After the system had been running continuously for 50 days, there were no obvious glassy deposits on the inner walls of the pipes and equipment, and the pressure differential of the bag filter dust collection system was 1.7 kPa, indicating good operating condition.

[0039] Example 2 Based on Example 1, in step (1), the organic polymer modification component (with polysulfone polymer as the main chain, naphthyl side group and imide functional group).

[0040] Product performance testing The composition of the final antimony white product of Example 2 was analyzed by X-ray fluorescence spectroscopy (XRF) and inductively coupled plasma mass spectrometry (ICP-MS), and the results are shown in Table 2.

[0041] Table 2

[0042] Note: Other components mainly consist of Na2O, MgO, SiO2, and small amounts of Fe, Cu, and other impurities, totaling 100%.

[0043] Based on material balance calculations, the Sb2O3 recovery rate in this Example 2 was 81.0%, and the As2O3 removal rate was 92.8%.

[0044] Example 3 Based on Example 1, in step (1), the organic polymer modification component (with polysulfone polymer as the main chain, triphenylmethane side group and containing trifluoromethyl functional group).

[0045] Product performance testing The composition of the final antimony white product of Example 3 was analyzed by X-ray fluorescence spectroscopy (XRF) and inductively coupled plasma mass spectrometry (ICP-MS), and the results are shown in Table 3.

[0046] Table 3

[0047] Note: Other components mainly consist of Na2O, MgO, SiO2, and small amounts of Fe, Cu, and other impurities, totaling 100%.

[0048] Based on material balance calculations, the Sb2O3 recovery rate in Example 3 was 79.5%, and the As2O3 removal rate was 90.2%.

[0049] Comparative Example 1 The difference from Example 1 is that a traditional electrostatic precipitator is used instead of a special coated filter bag. The working voltage of the electrostatic precipitator is 55kV and the electrode spacing is 300mm. Everything else is the same as in Example 1.

[0050] Product performance testing The composition of the final antimony white product of Comparative Example 1 was analyzed by X-ray fluorescence spectroscopy (XRF) and inductively coupled plasma mass spectrometry (ICP-MS), and the results are shown in Table 4.

[0051] Table 4

[0052] Note: Other components mainly consist of Na2O, MgO, SiO2, and small amounts of Fe, Cu, and other impurities, totaling 100%.

[0053] Based on material balance calculations, the Sb2O3 recovery rate in this comparative example was 69.0%, and the As2O3 removal rate was 75.0%.

[0054] It can be seen that the polar selective coated filter bag used in Embodiment 1 of the present invention has a significantly superior arsenic and antimony separation effect compared with the traditional electrostatic precipitator.

[0055] Comparative Example 2 The difference from Example 1 is that single-stage rapid air cooling is used instead of gradient air cooling, that is, in step (2), the flue gas is directly cooled from 295°C to 155°C at a cooling rate of 5°C / s, without segmented temperature control, and the rest is the same as Example 1.

[0056] result: On day 12 of operation, this comparative example showed obvious white glassy deposits, approximately 8-15 mm thick, on the inner wall of the pipes (especially from the quench tower outlet to the bag filter inlet). The system operating pressure differential increased from the initial 1.2 kPa to 3.8 kPa, and even with the induced draft fan frequency increased to 95% of full load, the designed airflow could not be maintained. By day 15, the effective flow area of ​​the pipes had decreased by approximately 60%, forcing the system to be shut down for manual cleaning. During the cleaning process, it was found that the glassy deposits were very hard, and even a combination of high-pressure water flushing and mechanical scraping was insufficient to completely remove them, with each cleaning session taking approximately 36 hours.

[0057] In Example 1, the gradient air cooling scheme of the present invention was adopted. When the system was running continuously for 50 days, only a very small amount of loose dust was deposited on the inner wall of the pipe (which can be removed by online backflushing). The system operating pressure difference slowly increased from the initial 1.2 kPa to 1.7 kPa, which was still far below the design warning value (2.5 kPa). The system was in good operating condition and was expected to continue to operate stably for more than 90 days.

[0058] As can be seen, the gradient air cooling strategy of rapidly crossing the glassy sensitive temperature range and supplementing it with slow cooling to induce crystalline precipitation in Embodiment 1 of the present invention can effectively suppress the formation and deposition of As2O3 glass and significantly extend the continuous operation cycle of the system compared with the traditional single-stage rapid cooling scheme.

[0059] Comparative Example 3 The difference from Example 1 is that process water spray cooling is used instead of air quenching, that is, in step (2), the flue gas is directly sprayed from 295°C to 155°C. The rest is the same as Example 1.

[0060] result: During a shutdown inspection on the 90th day of operation, this comparative example revealed extensive and uniform corrosion and pitting on the inner wall of the quench tower and the outlet pipe, with corrosion pits reaching depths of 1-3 mm. The stainless steel induced draft fan blades showed obvious corrosion pitting and erosion wear marks. The carbon steel pipe at the inlet of the bag filter dust collection system had a wall thickness reduction of approximately 1.5 mm (originally 6 mm). Based on the assessment, the estimated service life of the system's key equipment is less than 2 years, far below the normal design life (8-10 years).

[0061] In Example 1, air cooling was used. After 90 days of system operation, no obvious signs of corrosion were observed on the inner walls of the quench tower and pipes, and the equipment was in good condition. This demonstrates that using air as the cooling medium instead of process water spray can fundamentally avoid the corrosion problem caused by acidic condensate and significantly extend the service life of the equipment.

[0062] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A process for removing arsenic and recovering antimony white from low-purity antimony oxide powder, characterized in that, Includes the following steps: (1) One-time dust collection The low-purity antimony oxygen powder flue gas is cooled to 280-310℃ by air and then sent into a special membrane-coated bag dust collection system for primary dust collection to recover Sb2O3 dust. The coating layer of the special coated bag is a surface polarity-controlled composite coating material. The composite coating material includes polytetrafluoroethylene body and an organic polymer modified component dispersed in the polytetrafluoroethylene body. The molecular chain of the organic polymer modified component contains aromatic large side groups and polar functional groups. (2) Gradient air cooling The flue gas discharged after dust collection in step (1) is sent into a multi-stage gradient air quench tower, where air is used as the cooling medium to perform gradient cooling to 150-160℃. (3) Secondary dust collection The cooled flue gas from step (2) is sent to a baghouse dust collection system for secondary dust collection to recover antimony-oxygen dust and obtain antimony white product.

2. The process for removing arsenic and recovering antimony white from low-purity antimony oxygen powder as described in claim 1, characterized in that, In step (1), the aromatic macroside group is selected from at least one of phenyl, naphthyl, fluorenyl and triphenylmethane.

3. The process for removing arsenic and recovering antimony white from low-purity antimony oxygen powder as described in claim 1, characterized in that, In step (1), the polar functional group is selected from at least one of sulfone, imide, and trifluoromethyl.

4. The process for removing arsenic and recovering antimony white from low-purity antimony oxygen powder as described in claim 1, characterized in that, In step (1), the micropore size of the coating layer is 0.1-3.5 μm and the porosity is 75-90%.

5. The process for removing arsenic and recovering antimony white from low-purity antimony oxygen powder as described in claim 1, characterized in that, In step (1), the organic polymer modified component accounts for 8-15% of the total mass of the coating layer, and the polytetrafluoroethylene vinyl body accounts for 85-92% of the total mass of the coating layer; the organic polymer modified component forms polar enrichment micro-regions in the coating layer.

6. The process for removing arsenic and recovering antimony white from low-purity antimony oxygen powder as described in claim 1, characterized in that, In step (1), the inlet temperature of the primary dust collector is 295-305℃.

7. The process for removing arsenic and recovering antimony white from low-purity antimony oxygen powder as described in claim 1, characterized in that, In step (2), the gradient cooling specifically involves: First stage rapid cooling: The flue gas is rapidly cooled from 280-310℃ to 255-265℃, with a cooling rate of 10-15℃ / s and a residence time of ≤1.5s; The second stage of slow cooling: the flue gas is slowly cooled from 255-265℃ to 150-160℃ at a cooling rate of 1-2℃ / s.

8. The process for removing arsenic and recovering antimony white from low-purity antimony oxygen powder as described in claim 1, characterized in that, In step (2), the low-grade As2O3 dust that settles at the bottom of the air quench tower is recovered.

9. The process for removing arsenic and recovering antimony white from low-purity antimony oxygen powder as described in claim 1, characterized in that, In step (3), the antimony white product contains 74%-81% Sb2O3, 3%-5% As2O3, 0.02%-0.4% Bi (based on elements), and 0.1%-1% Pb (based on elements).